Local Governance of Peatland Restoration in Riau, Indonesia A Transdisciplinary Analysis - Okamoto, Masaaki; Osawa, Takamasa; Prasetyawan, Wahyu; Binawan, Akhwan (Global Environmental Studies,, 2023)
This open access book is one in a series of four volumes introducing peatland conservation and restoration in Indonesia. It focuses on local governance, in particular on regional and local perspectives in Riau, the most peat-destructed province of Indonesia. The book fills a vital gap in the existing literature that overlooks social science and humanities perspectives. Written by authors from different disciplines and backgrounds (including scholars and NGO activists), the approaches to the topic are various and unique, including analysis of GPS logs, social media, geospatial assessments, online interviews (conducted due to the Covid-19 pandemic), and more conventional questionnaires and surveys of community members. The chapters cover an interdisciplinary understanding of peatland destruction and broadly offer insights into environmental governance. While presenting combined studies of established fieldwork methodologies and contemporary technology such as drones and geospatial information, the book also explores the potential of long-distance research with rural communities through online facilitation, which was brought about by Covid-19, but that may have longterm implications. Readers will gain a comprehensive understanding of the complexities surrounding peatland conservation and restoration and recognize the significance of locally inclusive approaches that use contemporary but accessible technologies to sustainably govern the globally important resource of peatland. That approach would be useful for other environmentally fragile but important regions and give some ideas to achieve the United Nations' SDGs for 1)No Poverty, 5)Gender Equality, 13)Climate Action, 15)Life of Land.